Pension Funding in the Public Sector - Mitchell, Olivia S.; Smith, Robert S. (The Review of Economics and Statistics, 1994)
This paper explores the determinants of pension funding in the public sector. We formulate and test several hypotheses about the determinants of public employer pension funding practices, using a new data set describing financial and other characteristics of state, local, and teacher plans. The data show that, on average, public sector pension plans were relatively well-funded during the late 1980s. There were, however, wide variations in funding practices in our sample. Our analysis of these variations suggests that past funding practice tends to be perpetuated, that unionized employers are less likely to fully fund future pension obligations, and that funding is sensitive to fiscal pressure.